MiR-663a Stimulates Proliferation and Suppresses Early Apoptosis of Human Spermatogonial Stem Cells by Targeting NFIX and Regulating Cell Cycle - Fan Zhou; Qingqing Yuan; Wenhui Zhang; Minghui Niu; Hongyong Fu; Qianqian Qiu; Guoping Mao; Hong Wang; Liping Wen; Hongxiang Wang; Mujun Lu; Zheng Li; et al. (Elsevier, 2018)
Human spermatogonial stem cells (SSCs) could have significant applications in reproductive medicine and regenerative medicine because of their great plasticity. The fate determinations of human SSCs are mediated by epigenetic factors. However, nothing is known about the regulation of non-coding RNA on human SSCs. Here we have explored for the first time the expression, function, and target of miR-663a in human SSCs. MiR-663a was upregulated in human spermatogonia compared with pachytene spermatocytes, as indicated by microRNA microarray and real-time PCR. CCK-8 and 5-Ethynyl-2'-deoxyuridine (EDU) assays revealed that miR-663a stimulated cell proliferation and DNA synthesis of human SSCs. Annexin V and propidium iodide (PI) staining and flow cytometry demonstrated that miR-663a inhibited early and late apoptosis of human SSCs. Furthermore, NFIX was predicted and verified as a direct target of miR-663a. NFIX silencing led to an enhancement of cell proliferation and DNA synthesis and a reduction of the early apoptosis of human SSCs. NFIX silencing neutralized the influence of miR-663a inhibitor on the proliferation and apoptosis of human SSCs. Finally, both miR-663a mimics and NFIX silencing upregulated the levels of cell cycle regulators, including Cyclin A2, Cyclin B1, and Cyclin E1, whereas miR-663a inhibitor had an adverse effect. Knockdown of Cyclin A2, Cyclin B1, and Cyclin E1 led to the decrease in the proliferation of human SSCs. Collectively, miR-663a has been identified as the first microRNA that promotes the proliferation and DNA synthesis and suppresses the early apoptosis of human SSCs by targeting NFIX via cell cycle regulators Cyclin A2, Cyclin B1, and Cyclin E1. This study thus provides novel insights into the molecular mechanisms underlying human spermatogenesis, and it could offer novel targets for treating male infertility and other human diseases. Keywords: miRNA-663a, human spermatogonial stem cells, proliferation, apoptosis, NFIX, cell cycle proteins